Modern weapons and military equipment for issue 3-2016 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The importance of the group for the construction and testing of arms, ammunition and equipment in the unit for special purposes:O tasks, activities and actions performed by a group of technicians for the construction and testing of arms, ammunition and equipment in the unit for special purposes.